AB0470 A Research Evaluating the Effectiveness and the Side Effects of High Dose Methotrexate Use in Combined Therapy of Rheumatoid Arthritis. (10th June 2014) - Aydin Tufan, M.; Ersozlu Bozkırlı, E.D.; Kart Koseoglu, H.; Yucel, A.E.
Abstract : Background: When not treated properly, Rheumatoid arthritis (RA) progresses in its chronic course, joint damage increases, and it can even lead to systemic involvement. Methotrexate (MTX), is the most preferred drug in RA treatment. However, there is no agreement among physicians on the dose of methotrexate. Objectives: The aim of this study was to determine the effects and side effects of high dose methotrexate use in the initial combined therapy on the activity of disease among active RA patients. Methods: Newly diagnosed 45 RA patients were divided into two groups randomly. First group received 12, 5 mg/week MTX im for four weeks and continued orally. Second group received 25 mg/week MTX im for four weeks and continued with 12, 5 mg/week orally. Beside the MTX treatment, 2 gr/day SLZ and 5 mg/day prednisolone were given to both groups. At three different stages of the treatment patients were evaluated in terms of DAS28, MHAQ, VAS, morning stiffness, ESR and CRP. Results: Patients were 34 female and 11 male. Mean disease duration was 14.7 months. In 1st group, mean DAS28 was 6.51 at the beginning, and in the end of the 3rd month it decreased to 2.75. In second group, mean DAS28 was 6.05 at the beginning, and in the end of the 3rd month it decreased to 3.56. Tender joint count in second group was 3.17 at the 3rd month, whereas it was 1.64 at the first group. In the 3rd month, at the high dose MTX group, VAS, DAS28 showed statistically significant improvement when compared to parameters of other group. CRP, morning stiffness, swollen joint count, and MHAQ scores at the 25mg/week MTX group were better at the 1st and 3rd months; however, there was no statistically significant difference between two groups in terms of those parameters. Three patients had nausea, fatigue, vomiting. At the 3rd month, at first group treatment was changed in one patient only. At second group, treatment was changed in 4 patients. In one patient, nausea and vomiting developed and ALT increased in another patient. Although scores of 1st month didn't show a significant difference between two groups, scores of 3rd month in the high dose MTX group exhibited a marked improvement in all criteria except morning stiffness. Improvements in DAS28 and number of sensitive joints were statistically significant. ACR 20, 50, 70 and 90 improvements of 3rd month in the high dose MTX group were higher than those of first group. Conclusions: In 2010, a new classification criteria for RA was developed, which makes early diagnosis of RA possible. The treatment includes the use of MTX plus combined DMARDs at the early stages of active disease. Findings of this study demonstrated that usage of high dose MTX at an early stage is more effective in controlling the disease activity and increases the quality of life in RA. Patients receiving high dose metotrexate, needed less treatment change at the end of the 3rd month. References: Griffin AJ, Erkeller-Yuksel F. Parenteral methotrexate should be given before biological therapy. Rheumatology (Oxford). 2004 May;43(5):678-9. Miyasaka N.Paradigm shift and future perspectives in rheumatoid arthritis.Nihon Rinsho. 2013 Jul;71(7):1141-6. Review. Japanese Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3135